+0  
 
0
180
3
avatar

Prove that if w,z are complex numbers such that |w|=|z|=1 and wz≠1, then {w+z}/{1+wz} is a real number. How would I prove this using the complex plane?

Guest Mar 1, 2018
 #1
avatar+20164 
+1

I assume:

Prove that if \(w,z \) are complex numbers such that \(|w|=|z|=1\)

and  \(wz\ne -1\), then

\(\frac{w+z}{1+wz}\) is a real number.


\(\text{Let $w = \cos(\theta)+ \imath \sin(\theta)$ } \\ \text{Let $z = \cos(\phi) + \imath\sin(\phi)$ }\)

 

\(\begin{array}{|rcll|} \hline w+z &=& \cos(\theta)+ \imath \sin(\theta) + \cos(\phi) + \imath\sin(\phi) \\ &=& \Big(\cos(\theta)+ \cos(\phi)\Big) + \imath \Big( \sin(\theta) + \sin(\phi) \Big) \\\\ w\cdot z &=& \Big(\cos(\theta)+ \imath \sin(\theta) \Big) \Big( \cos(\phi) + \imath\sin(\phi) \Big) \\ &=& \cos(\theta)\cos(\phi) + \imath\sin(\phi)\cos(\theta) + \imath \sin(\theta)\cos(\phi) + \imath^2 \sin(\theta)\sin(\phi) \\ &=& \cos(\theta)\cos(\phi)+ \imath^2 \sin(\theta)\sin(\phi) + \imath \Big(\sin(\theta)\cos(\phi) + \sin(\phi)\cos(\theta) \Big) \\ && | \quad \imath^2 = -1 \\ &=& \underbrace{\cos(\theta)\cos(\phi)- \sin(\theta)\sin(\phi)}_{=\cos(\theta+\phi)} + \imath \Big(\underbrace{\sin(\theta)\cos(\phi) + \sin(\phi)\cos(\theta)}_{=\sin(\theta+\phi)} \Big) \\ &=& \cos(\theta+\phi) + \imath \sin(\theta+\phi) \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline && \dfrac{w+z}{1+wz} \\\\ &=& \dfrac{ \Big(\cos(\theta)+ \cos(\phi)\Big) + \imath \Big( \sin(\theta) + \sin(\phi) \Big) } { 1+\cos(\theta+\phi) + \imath \sin(\theta+\phi) } \\\\ &=& \dfrac{ \Big(\cos(\theta)+ \cos(\phi)\Big) + \imath \Big( \sin(\theta) + \sin(\phi) \Big) } { \Big(1+\cos(\theta+\phi)\Big) + \imath \sin(\theta+\phi) } \\ && | \quad \small{\text{ Multiply top and bottom by the conjugate}} \\\\ &=& \left[ \dfrac{\Big(\cos(\theta)+ \cos(\phi)\Big) + \imath \Big( \sin(\theta) + \sin(\phi) \Big) } { \Big(1+\cos(\theta+\phi)\Big) + \imath \sin(\theta+\phi) } \right] \left[ \dfrac{\Big(1+\cos(\theta+\phi)\Big) - \imath \sin(\theta+\phi) } { \Big(1+\cos(\theta+\phi)\Big) - \imath \sin(\theta+\phi) } \right] \\\\ &=& \dfrac{ \left[\Big(\cos(\theta)+ \cos(\phi)\Big) + \imath \Big( \sin(\theta) + \sin(\phi) \Big)\right] \left[\Big(1+\cos(\theta+\phi)\Big) - \imath \sin(\theta+\phi) \right] } { \Big(1+\cos(\theta+\phi)\Big)^2 - \imath^2 \sin^2(\theta+\phi) } \\\\ &=& \dfrac{ \left[\Big(\cos(\theta)+ \cos(\phi)\Big) + \imath \Big( \sin(\theta) + \sin(\phi) \Big)\right] \left[\Big(1+\cos(\theta+\phi)\Big) - \imath \sin(\theta+\phi) \right] } { \Big(1+\cos(\theta+\phi)\Big)^2 + \sin^2(\theta+\phi) } \\\\ &=& \dfrac{\Big(\cos(\theta)+ \cos(\phi)\Big)\Big(1+\cos(\theta+\phi)\Big) -\Big(\cos(\theta)+ \cos(\phi)\Big) \imath \sin(\theta+\phi) \\ +\imath \Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) -\imath \Big( \sin(\theta) + \sin(\phi) \Big) \imath \sin(\theta+\phi) } { \Big(1+\cos(\theta+\phi)\Big)^2 + \sin^2(\theta+\phi) } \\\\ &=& \dfrac{\Big(\cos(\theta)+ \cos(\phi)\Big)\Big(1+\cos(\theta+\phi)\Big) -\imath \Big(\cos(\theta)+ \cos(\phi)\Big) \sin(\theta+\phi) \\ +\imath \Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) -\imath^2 \Big( \sin(\theta) + \sin(\phi) \Big)\sin(\theta+\phi) } { \Big(1+\cos(\theta+\phi)\Big)^2 + \sin^2(\theta+\phi) } \\\\ &=& \dfrac{\Big(\cos(\theta)+ \cos(\phi)\Big)\Big(1+\cos(\theta+\phi)\Big) + \Big( \sin(\theta) + \sin(\phi) \Big)\sin(\theta+\phi) \\ -\imath \Big(\cos(\theta)+ \cos(\phi)\Big) \sin(\theta+\phi) +\imath \Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) } { \Big(1+\cos(\theta+\phi)\Big)^2 + \sin^2(\theta+\phi) } \\\\ &=& \dfrac{\Big(\cos(\theta)+ \cos(\phi)\Big)\Big(1+\cos(\theta+\phi)\Big) + \Big( \sin(\theta) + \sin(\phi) \Big)\sin(\theta+\phi) \\ +\imath \left[ \Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) - \Big(\cos(\theta)+ \cos(\phi)\Big) \sin(\theta+\phi) \right] } { \Big(1+\cos(\theta+\phi)\Big)^2 + \sin^2(\theta+\phi) } \\ \hline \end{array}\)

 

The imaginary part of the top line, showing that it's equal to zero:

\(\begin{array}{|rcll|} \hline \imath \left[ \underbrace{\Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) - \Big(\cos(\theta)+ \cos(\phi)\Big) \sin(\theta+\phi) }_{= 0\ ?}\right] \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) -\Big(\cos(\theta)+ \cos(\phi)\Big) \sin(\theta+\phi) \\\\ &=& \sin(\theta) + \sin(\phi) \\ &\qquad +& \sin(\theta)\cos(\theta+\phi) \\ &\qquad +& \sin(\phi)\cos(\theta+\phi) \\ &\qquad -& \cos(\theta)\sin(\theta+\phi) \\ &\qquad -& \cos(\phi)\sin(\theta+\phi) \\\\ &\qquad & \boxed{\cos(\theta+\phi) = \cos(\theta)\cos(\phi)- \sin(\theta)\sin(\phi) \\ \sin(\theta+\phi) = \sin(\theta)\cos(\phi) + \sin(\phi)\cos(\theta)} \\\\ &=& \sin(\theta) + \sin(\phi) \\ &\qquad +& \sin(\theta)\Big( \cos(\theta)\cos(\phi)- \sin(\theta)\sin(\phi) \Big) \\ &\qquad +& \sin(\phi)\Big( \cos(\theta)\cos(\phi)- \sin(\theta)\sin(\phi) \Big) \\ &\qquad -& \cos(\theta)\Big( \sin(\theta)\cos(\phi) + \sin(\phi)\cos(\theta) \Big) \\ &\qquad -& \cos(\phi)\Big( \sin(\theta)\cos(\phi) + \sin(\phi)\cos(\theta) \Big) \\\\ &=& \sin(\theta) + \sin(\phi) \\ &\qquad +& \sin(\theta)\cos(\theta)\cos(\phi)- \sin(\theta)\sin(\theta)\sin(\phi) \\ &\qquad +& \sin(\phi)\cos(\theta)\cos(\phi)- \sin(\phi)\sin(\theta)\sin(\phi) \\ &\qquad -& \cos(\theta)\sin(\theta)\cos(\phi) - \cos(\theta)\sin(\phi)\cos(\theta) \\ &\qquad -& \cos(\phi)\sin(\theta)\cos(\phi) - \cos(\phi)\sin(\phi)\cos(\theta) \\\\ &=& \sin(\theta) + \sin(\phi) \\ &\qquad +& \sin(\theta)\cos(\theta)\cos(\phi)- \sin^2(\theta)\sin(\phi) \\ &\qquad +& \sin(\phi)\cos(\theta)\cos(\phi)- \sin^2(\phi)\sin(\theta) \\ &\qquad -& \cos(\theta)\sin(\theta)\cos(\phi) - \cos^2(\theta)\sin(\phi) \\ &\qquad -& \cos(\phi)\sin(\phi)\cos(\theta) - \cos^2(\phi)\sin(\theta) \\\\ &=& \sin(\theta) + \sin(\phi) \\ &\qquad +& -\sin(\theta)\Big( \underbrace{\sin^2(\phi)+ \cos^2(\phi)}_{=1} \Big) \\ &\qquad +& - \sin(\phi)\Big( \underbrace{\sin^2(\theta)+\cos^2(\theta)}_{=1} \Big) \\ &\qquad +& \underbrace{\sin(\theta)\cos(\theta)\cos(\phi) - \sin(\theta)\cos(\theta)\cos(\phi)}_{=0} \\ &\qquad +& \underbrace{\sin(\phi)\cos(\phi)\cos(\theta) - \sin(\phi)\cos(\phi)\cos(\theta)}_{=0} \\\\ &=& \sin(\theta) + \sin(\phi) -\sin(\theta) - \sin(\phi) \\ &=& 0 \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \imath \left[ Big( \sin(\theta) + \sin(\phi) \Big)\Big(1+\cos(\theta+\phi)\Big) - \Big(\cos(\theta)+ \cos(\phi)\Big) \sin(\theta+\phi) \right] = 0 \\ \hline \end{array}\)

 

see link: https://web2.0calc.com/questions/prove-that-if-w-z-are-complex-numbers-such-that-w

 

laugh

heureka  Mar 2, 2018
edited by heureka  Mar 2, 2018
 #2
avatar+20164 
0

2. Solution:

 

I asume:
Prove that if \(w,z\) are complex numbers such that \(|w|=|z|=1\)
and
\(wz\ne -1\), then
\(\frac{w+z}{1+wz}\) is a real number.

 

\(\text{Let $w = a+\imath b \qquad a^2+b^2 = 1\quad (|w|=1)$ } \\ \text{Let $z = c+\imath d \qquad c^2+d^2 = 1\quad (|z|=1) $ }\)

 

\(\begin{array}{|rcll|} \hline w+z &=& a+\imath b + c+\imath d \\ &=& (a+c) + \imath( b + d) \\\\ w\cdot z &=& (a+\imath b) + (c+\imath d) \\ &=& (ac-bd)+\imath(ad+bc) \\ \hline \end{array}\)

 

\(\small{ \begin{array}{|rcll|} \hline && \dfrac{w+z}{1+wz} \\\\ &=& \dfrac{ (a+c) + \imath( b + d) } { 1+(ac-bd)+\imath(ad+bc) } \\\\ &=& \dfrac{ (a+c) + \imath( b + d) } { (1+ac-bd)+\imath(ad+bc) } \\ && | \quad \small{\text{ Multiply top and bottom by the conjugate}} \\\\ &=& \left[ \dfrac{ (a+c) + \imath( b + d) } { (1+ac-bd)+\imath(ad+bc) } \right] \left[ \dfrac{(1+ac-bd)-\imath(ad+bc)} { (1+ac-bd)-\imath(ad+bc) } \right] \\\\ &=& \dfrac{ \left[(a+c) + \imath( b + d)\right] \left[(1+ac-bd)-\imath(ad+bc) \right] } { (1+ac-bd)^2 - \imath^2 (ad+bc)^2 } \\\\ && \quad | \quad \imath^2=-1 \\\\ &=& \dfrac{ (a+c)(1+ac-bd) -\imath(a+c)(ad+bc) +\imath( b + d)(1+ac-bd)-\imath( b + d)\imath(ad+bc) } { (1+ac-bd)^2 + (ad+bc)^2 } \\\\ &=& \dfrac{ (a+c)(1+ac-bd) -\imath(a+c)(ad+bc) +\imath2( b + d)(1+ac-bd)-\imath^2( b + d)(ad+bc) } { (1+ac-bd)^2 + (ad+bc)^2 } \\\\ && \quad | \quad \imath^2=-1 \\\\ &=& \dfrac{ (a+c)(1+ac-bd) -\imath(a+c)(ad+bc) +\imath2( b + d)(1+ac-bd)+( b + d)(ad+bc) } { (1+ac-bd)^2 + (ad+bc)^2 } \\\\ &=& \dfrac{ (a+c)(1+ac-bd)+( b + d)(ad+bc) + \imath \Big(( b + d)(1+ac-bd)-(a+c)(ad+bc) \Big) } { (1+ac-bd)^2 + (ad+bc)^2 } \\ \hline \end{array} } \)

 

The imaginary part of the top line, showing that it's equal to zero:

\(\begin{array}{|rcll|} \hline \imath \left[ \underbrace{ ( b + d)(1+ac-bd)-(a+c)(ad+bc) }_{= 0\ ?}\right] \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline && (b + d)(1+ac-bd)-(a+c)(ad+bc) \\\\ &=& b+abc-b^2d+d+acd-d^2b -(a^2d+abc+acd+c^2b ) \\ &=& b+\not{ab}c-b^2d+d+\not{acd}-d^2b -a^2d-\not{abc}-\not{acd}-c^2b \\ &=& b-b^2d+d -d^2b -a^2d -c^2b \\ &=& b+d -b(\underbrace{c^2+d^2}_{=1})-d(\underbrace{a^2+b^2}_{=1}) \\ &=& b+d -b -d \\ &=& 0 \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \imath \left[ ( b + d)(1+ac-bd)-(a+c)(ad+bc) \right] = 0 \\ \hline \end{array} \)

 

laugh

heureka  Mar 2, 2018
 #3
avatar
0

Could you explain the last 3 steps in the second part of #2 solution? Im not sure how you got the two.

Guest Mar 2, 2018
edited by Guest  Mar 2, 2018
edited by Guest  Mar 2, 2018

31 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.